Pseudomonas aeruginosa in Cancer Therapy: Current Knowledge, Challenges and Future Perspectives - Pang, Zheng; Gu, Meng-Di; Tang, Tong (Frontiers in Oncology, 2022)
Drug resistance, undesirable toxicity and lack of selectivity are the major challenges of conventional cancer therapies, which cause poor clinical outcomes and high mortality in many cancer patients. Development of alternative cancer therapeutics are highly required for the patients who are resistant to the conventional cancer therapies, including radiotherapy and chemotherapy. The success of a new cancer therapy depends on its high specificity to cancer cells and low toxicity to normal cells. Utilization of bacteria has emerged as a promising strategy for cancer treatment. Attenuated or genetically modified bacteria were used to inhibit tumor growth, modulate host immunity, or deliver anti-tumor agents. The bacteria-derived immunotoxins were capable of destructing tumors with high specificity. These bacteria-based strategies for cancer treatment have shown potent anti-tumor effects both in vivo and in vitro, and some of them have proceeded to clinical trials. Pseudomonas aeruginosa, a Gram-negative bacterial pathogen, is one of the common bacteria used in development of bacteria-based cancer therapy, particularly known for the Pseudomonas exotoxin A-based immunotoxins, which have shown remarkable anti-tumor efficacy and specificity. This review concisely summarizes the current knowledge regarding the utilization of P. aeruginosa in cancer treatment, and discusses the challenges and future perspectives of the P. aeruginosa-based therapeutic strategies.